2008
DOI: 10.1001/archderm.144.12.1597
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopic and Histopathologic Correlations of Dermoscopic Features in 202 Melanocytic Lesions

Abstract: Objectives: To identify in vivo microscopic substrates of the dermoscopic patterns of melanocytic lesions and to correlate them with histopathologic features.Design: Before excision, lesion areas that showed characteristic dermoscopic patterns were imaged by dermoscopy and confocal microscopy and directly correlated with histopathologic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 30 publications
6
151
0
5
Order By: Relevance
“…21 Evidence of stromal remodeling can also be identified with reflectance confocal microscopy by visualizing bundles of collagen fibers that histopathologically correspond to fibroplasia and to regression structures on dermatoscopy. 22,23 Type I collagen with extracellular matrix glycoproteins, such as tenascin C and fibronectin, have been shown to facilitate dermal invasion during the more advanced vertical growth phase by forming tubular channels that ensheath and isolate invading melanoma cells. 24 Based on the available preclinical data, we hypothesize that CS may reflect de novo synthesis or remodeling of type I collagen in the papillary dermis, signifying changes Our retrospective analysis revealed that the presence of CS in melanomas was frequently associated with polymorphous vascular pattern (OR = 12.5) (Fig 5).…”
Section: Discussionmentioning
confidence: 99%
“…21 Evidence of stromal remodeling can also be identified with reflectance confocal microscopy by visualizing bundles of collagen fibers that histopathologically correspond to fibroplasia and to regression structures on dermatoscopy. 22,23 Type I collagen with extracellular matrix glycoproteins, such as tenascin C and fibronectin, have been shown to facilitate dermal invasion during the more advanced vertical growth phase by forming tubular channels that ensheath and isolate invading melanoma cells. 24 Based on the available preclinical data, we hypothesize that CS may reflect de novo synthesis or remodeling of type I collagen in the papillary dermis, signifying changes Our retrospective analysis revealed that the presence of CS in melanomas was frequently associated with polymorphous vascular pattern (OR = 12.5) (Fig 5).…”
Section: Discussionmentioning
confidence: 99%
“…On RCM, the architectural disarray at the dermal-epidermal junction, the diffuse dendritic and small bright cells corresponded to inflammation, and the large irregular blood vessels were not suggestive of either melanocytic or keratinocytic malignancy [2,3]. However, the presence of multinucleated keratinocytes with high refractile dots, distributed at the periphery close to the nuclear envelope, potentially suggested a viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopic examination (Molemax II, Derma Instruments, Vienna, Austria) of the lesion showed a periferic light brown irregular pigmentation, milia-like cysts and an atypical vascular pattern. In vivo reflectance confocal microscopy (RCM) (Vivascope 1500; Lucid Inc., Rochester, NY, USA) was performed at different depth levels to a maximum of 150 µm [1,2]; of concern was the observation in the epidermal layer of a diffuse pattern of single and multinucleated large keratinocytes, demarcated with sharp contours, containing bright grainy cytoplasm and round dark nuclei with bright dots close to the nuclear envelope in a ring pattern (Figure 2(a)). At the dermo-epidermal junction, cords of variable refractile cells arranged parallel to each other were observed, as were keratinocytes with thickened contours, different in size and refractivity and arranged with an atypical honeycomb pattern.…”
Section: Casementioning
confidence: 99%
“…Maximum penetration of the skin is 350µm [21,22]. Different skin cancers have different morphological features which can be distinguished by using CLSM in vivo and ex vivo, enabling it to be potentially used to give a real time diagnosis to the patients negating the need to wait for histopathology results [22,23]. There are many articles but only a limited number of studies on the use of CLSM in the diagnosis of skin cancer.…”
mentioning
confidence: 99%